The gut-liver axis mechanism of increased susceptibility to non-alcoholic fatty disease in female offspring rats with prenatal caffeine exposure - Qian Wang; Xiaoqian Lu; Wen Hu; Cong Zhang; Kexin Liu; Kai Tong; Kaiqi Chen; Hui Wang (Food Science and Human Wellness)
Caffeine intake during pregnancy is common, while its effect on gut microbiota composition of offspring and the relationship with susceptibility to adult diseases remains unclear. This study aimed to confirm the effects of prenatal caffeine exposure (PCE) on the gut microbiota composition and its metabolites in female offspring rats, and to further elucidate its underlying mechanism and intervention targets in adult non-alcoholic fatty disease (NAFLD). The results showed that the gut microbiota of PCE female offspring at multiple time points from infancy to adolescence were significantly changed with depletion of butyric acid-producing bacteria, leading to a decrease in butyric acid in adulthood. It was also found that PCE female offspring rats were sensitive to NAFLD induced by a postnatal high-fat diet (HFD), which is mainly related to the enhancement of hepatic triglyceride synthesis function. Through mechanism exploration, we found that HFD further reduced the fecal and serum butyric acid levels in the PCE female offspring, which was significantly negatively correlated with hepatic SREBP-1c/FASN mRNA expression and triglyceride level. In vivo and in vitro experiments confirmed that sodium butyrate (NaB) supplementation could reduce hepatic lipid accumulation through MCT1/GPR109A-AMPK, thereby effectively decreasing the susceptibility to NAFLD in the PCE female offspring rats.